1983
DOI: 10.1111/j.1432-1033.1983.tb07694.x
|View full text |Cite
|
Sign up to set email alerts
|

A pulse‐radiolysis study of the reduction of flavodoxin from Megasphaera elsdenii by viologen radicals. A conformational change as a possible regulating mechanism

Abstract: Pulse-radiolysis experiments were performed on solutions containing methyl or benzyl viologen and flavodoxin. Viologen radicals are formed after the pulse. The kinetics of the reaction of these radicals with flavodoxin were studied. The kinetics observed depend strongly on the concentration of oxidized viologen. Therefore one must conclude that a relatively stable intermediate is formed after the reduction of flavodoxin. The midpoint potential of the intermediate state is -(480 30) mV, and is hardly dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
(22 reference statements)
2
18
0
Order By: Relevance
“…Finally, the results support and extend the previous pulse radiolysis work (van Leeuwen et al, 1983) and demonstrate that proton release during the redox reaction of flavodoxin semiquinone and a one-electron acceptor proceeds at a much faster rate than the processes associated with the electrontransfer event (the latter would include any bond distance or bond angle changes or any changes in solvation that occur during the formation of the transition state). The pH independence of the reaction rate constant implies that the difference in flavodoxin semiquinone redox potential between low and high pH does not affect the reaction kinetics, even though it has previously been shown (Meyer et al, 1983;Cheddar et al, 1986;Tollin et al, 1986) that, at a given pH, redox potential differences do exert a measurable influence on the apparent second-order rate constants for electron transfer.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, the results support and extend the previous pulse radiolysis work (van Leeuwen et al, 1983) and demonstrate that proton release during the redox reaction of flavodoxin semiquinone and a one-electron acceptor proceeds at a much faster rate than the processes associated with the electrontransfer event (the latter would include any bond distance or bond angle changes or any changes in solvation that occur during the formation of the transition state). The pH independence of the reaction rate constant implies that the difference in flavodoxin semiquinone redox potential between low and high pH does not affect the reaction kinetics, even though it has previously been shown (Meyer et al, 1983;Cheddar et al, 1986;Tollin et al, 1986) that, at a given pH, redox potential differences do exert a measurable influence on the apparent second-order rate constants for electron transfer.…”
Section: Discussionsupporting
confidence: 82%
“…These data constitute strong evidence that the electron-transfer step is not coupled to proton release from the neutral flavin semiquinone during le-oxidation; Le., proton release proceeds much more rapidly than electron transfer (see below for further comment). van Leeuwen et al (1983) have observed that the rate of Megasphaera elsdenii flavodoxin reduction to the semiquinone by the radical form of methylviologen is pH independent between pH 7.0 and 9.2. This observation is also consistent with a kinetic "uncoupling" of electron transfer and protonation of the flavin; Le., the rate of protonation is much faster than the rate of one-electron reduction.…”
Section: Effect Of P H On the Rate Of Electron Transfermentioning
confidence: 97%
“…The values determined for the midpoint redox potentials of the two steps in the reduction of the recombinant protein are very similar to the values reported from two laboratories for the native protein [18,54]. However, two other reports have given values for the semiquinone/hydroquinone couple ( E 1 ) that are about 20 mV more negative [29,55], and a measurement by pulse radiolysis gave a value of −410 ± 30 mV [56]. Vervoort et al .…”
Section: Discussionsupporting
confidence: 81%
“…Anyway, if non-processed MLS-Fld displays lower or no function, it is possible that the achieved levels of Fld activity are insufficient to cope with MV challenge. Regarding this point van Leeuwen et al [56] have reported that the reaction of MV radicals with Fld increases with Fld concentration and decreases when the concentration of oxidized viologen raises. In our studies we could be in the presence of low Fld (unprocessed protein) and high oxidized MV levels (high MV concentration imposed) explaining our observations.…”
Section: Discussionmentioning
confidence: 97%